2009
DOI: 10.1111/j.1365-2486.2009.01919.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of plants and the dominant microarthropod,Cryptopygus antarcticus, to warming and contrasting precipitation regimes in Antarctic tundra

Abstract: We examined the influence of warming and supplemental precipitation on plant production and abundance of the dominant microarthropod, the springtail Cryptopygus antarcticus (Collembola), in tundra dominated by the vascular plants Colobanthus quitensis and Deschampsia antarctica along the Antarctic Peninsula. Tundra cores were placed in plots near Palmer Station where they were warmed with infrared heaters in combination with receiving supplemental precipitation. Diel canopy air and soil temperatures and air va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 51 publications
(91 reference statements)
3
53
1
1
Order By: Relevance
“…Soil fungi are more tolerant than bacteria to temperatures that are above optimum (Barcenas-Moreno et al 2009) and appear to increase their activity after a long-term increase of temperature, as indicated by fruit body production (Gange et al 2007). Organisms feeding on fungi are also more tolerant to elevated temperatures (Stamou and Sgardelis 1989;Maraun et al 2007) and increase in abundance when moisture is not a limiting factor (Day et al 2009;Kardol et al 2010). In general organisms belonging to the fungal-based food web channel have been found to be more resistant and better able to adapt to climate change associated with drought (de Vries et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Soil fungi are more tolerant than bacteria to temperatures that are above optimum (Barcenas-Moreno et al 2009) and appear to increase their activity after a long-term increase of temperature, as indicated by fruit body production (Gange et al 2007). Organisms feeding on fungi are also more tolerant to elevated temperatures (Stamou and Sgardelis 1989;Maraun et al 2007) and increase in abundance when moisture is not a limiting factor (Day et al 2009;Kardol et al 2010). In general organisms belonging to the fungal-based food web channel have been found to be more resistant and better able to adapt to climate change associated with drought (de Vries et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in Open Top Chambers (OTCs) carried out in three different locations on the Falkland, Signy, and Anchorage Island on cryptogamic communities showed no significant effect of warming on mosses [5]. In contrast, in situ experiments by Day et al [20,21] in vascular plant-dominated communities have determined a decrease in moss cover after 4 years of long term growth under passive warming on Anvers Island, along the Antarctic Peninsula. In these experiments, it is unclear whether warming directly decreases moss cover or whether increases in vascular plant cover caused by warming leads indirectly to decreases in moss cover.…”
Section: Introductionmentioning
confidence: 95%
“…Studies examining the impacts of simulated warming on plant-dwelling microarthropods in the WAP found that although ubiquitous in both mesic and extreme environments, Collembolans were particularly sensitive to changes in temperature and moisture Day et al, 2009). Recent work found that warming reduced Collembollan populations in an Antarctic lichen community (Bokhorst et al, 2015).…”
Section: Warming Does Not Impact Antarctic Moss Community Compositionmentioning
confidence: 99%